Pemahaman Dan Kepedulian Penerapan Green Accounting Pada Puskesmas Kecamatan Bluto Kabupaten Sumenep - Dicky Wahyudi; Syahril; Rusnani (Journal of Public and Business Accounting, 2022)
This study entitled "Understanding And Careful About The Implementation Of Green Accounting (Puskesmas Bluto)" is a study that aims to find out how the understanding and concern for the application of Green Accounting as a form or effort to reduce the impact on the environment caused by operational activities. Bluto then before and after the implementation of Green Accounting. This research was conducted at the Community Health Center, Bluto District, this type of research is a qualitative-descriptive research. The data sources were obtained through interviews with informants and the results of observations and then to test the validity of the data using triangulation of data sources and theories. The results of this study are (1) understanding and concern for the application of Green Accounting has been done well, it can be seen from the activities carried out by the Bluto Health Center in reducing the existing environmental impacts such as managing waste properly. (2) environmental costs arising from the operational activities of the puskesmas are recognized using the accrual basis method, then in measuring environmental costs using the previous budget realization (Historical Cost), and for requests for environmental costs, they must submit a RUK (Proposed Activity Plan) 1 year earlier and the following year must make an RPK (Activity Implementation Plan). (3) reporting prior to the application of Green Accounting at the Bluto Health Center, which has not made a special reporting presentation, where the environmental costs incurred are recognized as expenses and included in the operational report but after the application of Green Accounting the Bluto Health Center is able to present special financial reports on environmental costs and can already identify the environmental costs that arise at the Bluto Health Center.